The Algorithmic Scalpel: AI-Powered Intraoperative Decision Support Systems - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The operating room OR is a high-stakes environment where surgeons must make complex, time-sensitive decisions under immense pressure. Even the most experienc...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care